Design of interfaces for optimal mechanical properties in Al2O3/Mo laminated composites. Issue 3 (March 2015) - Song, Junjie; Zhang, Yongsheng; Fan, Hengzhong; Hu, Tianchang; Hu, Litian; Qu, Jianmin
Abstract High-performance Al2O3/Mo laminated composites are potential candidates for space applications because of their excellent self-lubricating and mechanical performance. This study aims at revealing the mechanisms of how interfacial morphology affects the mechanical properties of Al2O3/Mo laminated composites. Four types of micro-textures of different densities were produced by solid-state pulse Nd:YAG laser on the surface of a Al2O3 green body. Al2O3/Mo laminated composites with different interfacial morphologies were prepared by laser-texturing and hot-pressing. It is found that the self-locking function of a regular serrated interface improves the interfacial bonding strength and controls the residual stress of materials, thus realizing the optimization of materials. The toughness, work of fracture and strength of the materials could reach 8.0 MPa m1/2, 1179 J m−2 and 293 MPa, which were 2.1 times, 6.6 times and 1.2 times higher than those of monolithic Al2O3 ceramics, respectively.